Exploring the effect of land use on ecosystem services: the distributive issues - Lopes, Luís Filipe Gomes (2015)
The current debate of ecosystem services has focused more on monetary valuation methods and pay-ments for environmental services (PES) then on the classic economic analysis (i.e. assumptions regarding:sustainability, justice and efficiency). This paper examines, taking into consideration ecosystem services,income distribution from different land uses to stakeholders. We study the Portuguese common landecosystem, which is characterized as having a wide range of ecosystem services. Allowing that all thebenefits can be translated into economic value, we estimated the total economic value (TEV) associatedwith these territories on 5 different land use situations: forest, shrubland, water bodies, mountain agri-culture and other uses, and analyzed the current institutional arrangements around these territories.We found that the distribution of the benefits of different land uses is relatively inequality. The resultsshowed that the contemporary institutional arrangements of wealth distribution ensure a relatively fairdistribution insider of system; however this institutional arrangement is unable to ensure equitable dis-tribution of wealth by external stakeholders. We can conclude that different types of land use provide avery asymmetric distribution of income by different groups of humans: land owners; citizens of a country,and residents of Earth.